2022
DOI: 10.1039/d2fo00734g
|View full text |Cite
|
Sign up to set email alerts
|

Myricitrin – a flavonoid isolated from the Indian olive tree (Elaeocarpus floribundus) – inhibits Monoamine oxidase in the brain and elevates striatal dopamine levels: therapeutic implications against Parkinson's disease

Abstract: Flavonoids exhibit several biological activities including Monoamine oxidase (MAO) inhibition, an enzyme that metabolizes several neurotransmitters. Thus, MAO inhibitors are well included in traditional therapeutic practices to fine-tune neuromotor behavior....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Research has emphasized myricetin, a flavonoid that has shown inhibitory effects on MAO, indicating its ability to decrease MAO levels. 50 Apigenin, isoquercetrin, and quercetrin are well-recognized flavonoids that have shown neuroprotective and anti-inflammatory properties. 51 These flavonoids have the potential to increase the capacity of the extract to regulate MAO concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Research has emphasized myricetin, a flavonoid that has shown inhibitory effects on MAO, indicating its ability to decrease MAO levels. 50 Apigenin, isoquercetrin, and quercetrin are well-recognized flavonoids that have shown neuroprotective and anti-inflammatory properties. 51 These flavonoids have the potential to increase the capacity of the extract to regulate MAO concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Striatal tissue is prepared for DA level measurement following the protocol stated as earlier [ 84 ]. Sample is injected into a HPLC system (Thermo ultimate 3000) through a Rheodyne injector, equipped with a glassy carbon electrochemical detector.…”
Section: Methodsmentioning
confidence: 99%
“…Myricitrin’s therapeutic potential was examined in a mouse brain model by Banerjee et al In the mouse brain, myricitrin reduced MAO activity and increased DA levels. In the PD mouse model, myricitrin could lessen motor incoordination and elevate the DA levels in the striatum ( Banerjee et al, 2022 ).…”
Section: Phytoconstituents In Different Neurological Disordersmentioning
confidence: 99%